Development of Inquiry Model Interview Text Learning Application to Enhance Fourth Graders Speaking Skills - Musfirah, Nur Laila; Sismulyasih SB, Nugraheti (Tadris: Jurnal Keguruan dan Ilmu Tarbiyah, 2025)
The selection of appropriate learning media is essential to ensure high-quality education. Integrating technology into learning media fosters an engaging environment and enhances students’ comprehension. This study aimed to develop, validate, and evaluate the effectiveness of an inquiry-based learning application SILASWARA (Interview Text Learning Application), designed to improve speaking skills among fourth-grade students at SD Negeri Karangmulyo. Utilizing a Research and Development (R&D) approach based on the Borg and Gall model, the study involved teachers and students as participants. Data were collected through interviews, observations, documentation, and questionnaires. Expert validation revealed high feasibility, with media experts scoring 88.75% and material experts 95%, both categorized as “very feasible.” Effectiveness testing using a paired-sample t-test indicated a significant improvement (p = 0.000), with the average score increasing from 70.76 (pre-test) to 89.05 (post-test). The N-Gain score was 0.6639 (66.39%), reflecting a moderate yet meaningful effectiveness. These findings demonstrate that the SILASWARA application is both feasible and effective as a digital learning tool to enhance speaking skills. Furthermore, its implementation supports active student participation and fosters critical thinking in the learning process.